Effectiveness of Media Intelligence in Supporting the 2024 Regional Elections - Siboro, Trevian (Indonesian National Police Academy, 2024)
The 2024 Regional Elections in Indonesia, held in conjunction with legislative and presidential elections, mark a critical moment for democratic governance, presenting both opportunities and complex challenges in maintaining security and order. The simultaneous elections introduce new risks in the form of misinformation, computational propaganda, and cyber threats due to advancements in information technology and the spread of the post-truth phenomenon. In response, the Indonesian National Police have implemented